TRANSFORMASI PEMBELAJARAN BERBASIS MASALAH: USULAN MODEL PBL BARU UNTUK MENINGKATKAN KETERAMPILAN DAN KETERLIBATAN MAHASISWA - Setiawan, Irwan; Hutahaean, Jonner; Lian Min, Joe; Chandra Nugraha, Ade; Wisnuadhi, Bambang (Jurnal Penjaminan Mutu, 2024)
This study examines the effectiveness of a newly proposed Problem-Based Learning (PBL) model compared to the conventional approach among second-year students in the Diploma III Program in Informatics Engineering at Computer Engineering and Informatics Department POLBAN. While the conventional PBL model follows a linear approach, the new model introduces a two-stage learning process with a focus on group formation after the initial phase. The analysis encompasses problem-solving skills, perceptions, and student engagement in PBL. Findings indicate a significant superiority of the new PBL model over the conventional one. Notably, the new model reduces instances of free riders, and students initially categorized as low achievers exhibit notable improvement, transitioning to moderate achievers. Additionally, students initially classified as medium achievers progress to the good category. These results underscore the importance of active participation and individual development in enhancing educational outcomes. The study contributes insights into refining PBL methodologies to foster deeper student engagement and improve problem-solving abilities in higher education settings.